Poziom stresu związanego ze studiami i jego wybrane uwarunkowania = Levels of studying-related stress and its selected causation - Herberger, Jerzy (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The study examines levels of studying-related stress and its selected sources. Author reflects upon impacts of external resources (such as support received from family members) and internal resources (subjects' sense of coherence), as well as moderating factors (sex, type of studies: humanities vs. technical studies).
Keywords: stres; stres związany ze studiami; zasoby; poczucie koherencji; stress; studying-related stress; resources; sense of coherence